PLURALISM IN SETTING AND SIGNIFICATION OF PORNOGRAPHY - Erni Wulandari (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The body becomes an object of study from various sciences, also the sciences of law. Meanings of the body in a regulatory text, can not be separated from an understanding of the rule-making body itself. The body can not be defined as a single, so the text that put in order about body also should not be interpreted as a single. Hermeneutics as a branch of philosophy may help to understand the meaning contained in the text and as contextual. The dimension of something that violates decency or not always shifted from time to time, as well as in the issue of pornography. Using hermeneutics for explain the meaning behind the text which is adjusted to the era, can help law enforcement in seeking and find the truth and justice in prosecuting cases related to the issue of the body.Keywords: pornography, hermeneutics, body, the regulation of pluralism, commodification.